2014
DOI: 10.7182/pit2014289
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine as an Ethics Teaching Tool for Medical Students within the Nephrology Curriculum

Abstract: A novel patient-centered approach was used to deliver ethics curriculum to medical students. Two medical school clinicians designed a telemedicine session linking their facilities (across 2 continents). The session, Exploring the Patient Experience Through Telemedicine: Dialysis and End-Stage Renal Disease, allowed second-year medical students to explore various parameters of quality of life experienced by dialysis patients. A panel of 4 medical students interviewed a dialysis patient via Skype video connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…Collaborative learning in health care has evolved rapidly; the Institute for Healthcare Improvement’s collaborative learning model offers one leading example. 1 Telemedicine also allows long-distance training for health-care professionals, 2 an effective method to deliver patient-centred, contextual medical curricula, 3 and supportive supervision. Additionally, online social networking enables communities of practice 4 that “offer the potential to bring together temporally and geographically dispersed actors to work towards a common purpose”.…”
mentioning
confidence: 99%
“…Collaborative learning in health care has evolved rapidly; the Institute for Healthcare Improvement’s collaborative learning model offers one leading example. 1 Telemedicine also allows long-distance training for health-care professionals, 2 an effective method to deliver patient-centred, contextual medical curricula, 3 and supportive supervision. Additionally, online social networking enables communities of practice 4 that “offer the potential to bring together temporally and geographically dispersed actors to work towards a common purpose”.…”
mentioning
confidence: 99%
“…Where international rotations are not possible, other studies have shown that didactics or classroom‐based education can play a role in improving international health exposure and cultural appreciation . In a telemedicine‐based, patient‐case focused, ethics in nephrology curriculum, one study reported high trainee exposure to additional contextual features of medicine and cross‐cultural appreciation, illustrating that telemedicine could be used to address cultural sensitivity goals in education . These experiences demonstrate that international travel is not always necessary to obtain meaningful educational experiences in international health.…”
Section: Discussionmentioning
confidence: 99%
“…15,19 In a telemedicine-based, patient-case focused, ethics in nephrology curriculum, one study reported high trainee exposure to additional contextual features of medicine and cross-cultural appreciation, illustrating that telemedicine could be used to address cultural sensitivity goals in education. 20 These experiences demonstrate that international travel is not always necessary to obtain meaningful educational experiences in international health. Our study provides additional evidence that novel educational tools, such as teledermatology-based virtual grand rounds, can improve international health and cross-cultural medical training among residents while addressing ACGME core competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Bramstedt et al 17 presented a study assessing telemedicine as an ethics teaching tool for medical students in the nephrology curriculum. They found that telemedicine can be an effective and feasible method with which to deliver an ethics curriculum with a patient-centered approach.…”
Section: The Australian Experience With Videoconferencing-based Telenmentioning
confidence: 99%